Hermeneutic Features of Management Activities - Aslanov Said Karimovich (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
This article explores how philosophical principles such as ethics, power dynamics, and social responsibility intersect with management practices. By examining relational leadership, stakeholder engagement, and contemporary theories of corporate social responsibility (CSR), this study emphasizes that effective management is not only about enhancing efficiency and profitability but also about fostering meaningful relationships, promoting inclusivity, and ensuring sustainable development. The research discusses how social structures, communication forms, and ethical values shape managerial decisions, ultimately influencing organizational success and societal well-being. This approach allows for a deeper understanding of management as a social practice that transcends traditional economic and administrative perspectives. The article highlights the intersection of social philosophy and management, emphasizing the role of philosophical principles in informing management practices. It focuses on human relationships, ethical considerations, and the development of social capital within organizations. Through comprehensive literature review and theoretical analysis, the study underscores the importance of integrating philosophical values into management to enhance organizational efficiency and employee well-being. The socio-philosophical aspects of management emphasize the complex relationships between individuals, organizations, and society. A relational approach to management stresses the significance of social interactions, ethical reasoning, and cultural contexts in decision-making and organizational structures.